2012
DOI: 10.1074/jbc.m111.325928
|View full text |Cite
|
Sign up to set email alerts
|

Galactose Recognition by the Apicomplexan Parasite Toxoplasma gondii

Abstract: Background: TgMIC4 is an important microneme effector protein from Toxoplasma gondii. Results: The structure of TgMIC4 together with carbohydrate microarray analyses reveal a broad specificity for galactoseterminating sequences. Conclusion: Lectin activity within the fifth apple domain of TgMIC4 is reminiscent of the mammalian galectin family. Significance: TgMIC4 may contribute to parasite dissemination within the host or down-regulation of the immune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 60 publications
(87 reference statements)
0
43
0
Order By: Relevance
“…The probes were robotically printed in duplicate on nitrocellulose-coated glass slides at 2 and 5 fmol per spot using a non-contact instrument [38], [39]. The his-tagged recombinant VP1 protein was pre-complexed with mouse monoclonal anti-poly-histidine (Ab1) and biotinylated anti-mouse IgG antibodies (Ab2) (both from Sigma) in a ratio of 4∶2∶1 (by weight).…”
Section: Methodsmentioning
confidence: 99%
“…The probes were robotically printed in duplicate on nitrocellulose-coated glass slides at 2 and 5 fmol per spot using a non-contact instrument [38], [39]. The his-tagged recombinant VP1 protein was pre-complexed with mouse monoclonal anti-poly-histidine (Ab1) and biotinylated anti-mouse IgG antibodies (Ab2) (both from Sigma) in a ratio of 4∶2∶1 (by weight).…”
Section: Methodsmentioning
confidence: 99%
“…Genetic disruption of each one of these three genes does not interfere with parasite survival [8] nor its interaction with, and attachment to, host cells [10]; however, MIC1 has been shown to play a role in invasion and contributes to virulence in mice [10]. We previously isolated soluble MIC1/4, a lactose-binding complex from soluble T. gondii antigens (STAg) [17], and its lectin activity was confirmed by the ability of MIC1 to bind sialic acid [9] and MIC4 to β-galactose [18]. We also reported that MIC1/4 stimulates adherent splenic murine cells to produce IL-12 at levels as high as those induced by STAg [20].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that host-cell invasion by apicomplexan parasites such as T. gondii involves carbohydrate recognition [1215]. Interestingly, MIC1 and MIC4 have lectin domains [11, 1618] that recognize oligosaccharides with sialic acid and D-galactose in the terminal position, respectively. Importantly, the parasite’s Lac + subcomplex, consisting of MIC1 and MIC4, induces adherent spleen cells to release IL-12 [17], a cytokine critical for the protective response of the host to T. gondii infection [19].…”
Section: Introductionmentioning
confidence: 99%
“…3; 150 < ' < 170 and À10 < < 10 ). The TgMIC4 structure was determined by solution NMR, and LNB was modelled by calculation using a molecular docking program (HADDOCK) based on NOEderived distance restraints (Marchant et al, 2012). The type-1 A tetrasaccharide in GH98 EABase mutants contains an LNB in which the sugars adopt an L-shaped conformation (Fig.…”
Section: Glycosidic Bond Conformationsmentioning
confidence: 99%